Design of an Intelligent Feeding System - Huang, Guiyun; Chen, Ying; Li, Yong; Cui, Jian (Journal of physics. Conference series, 2024)
The article elaborates on the design method of an intelligent feeding system . The feeding system is an important part of the automatic production line, which provides raw materials for other units of the automatic production line. It is controlled by PLC, which is described from many aspects, such as structure design, pneumatic circuit design, control circuit design and PLC program design. It analyzes the design idea and principle of intelligent feeding system in detail, and provides an effective reference for the design of automatic production line.